UFG em todo lugar: apontamentos para uma política de comunicação pública da ciência - Basile, Roberta de Castro (2023)
At the Federal University of Goiás, extension was responsible for mediate dialogue and the exchange of knowledge between science and the population. By knowing some notions and practices of Public Communication of Science that permeate this finalistic sphere of federal universities, a qualitative, descriptive-exploratory research was proposed, with a case study. Based on the extension program “UFG em Todo Lugar”, for the popularization of science, the research sought to answer the question: what guidelines would be necessary to strengthen and make the actions of this program more effective? The study covers the program's past and present, using multiple collection instruments, among them, documental research, questionnaires, interviews and a focus group. The purpose was to know the perceptions about the Public Communication of Science (together with managers, organizers and extension teams that work in the program), the ways they use to bring science closer to the population, the difficulties of this trajectory, in addition to the opinions of the external public who participated in the event promoted on May 27, 2023. Together, these data also made it possible to identify the gaps of “UFG em Todo Lugar”, resulting in notes for a Public Science Communication Policy that could strengthen it. The data were systematized and presented according to Bardin's Content Analysis (2016), with a triangulation at the end. In this way, it offers not only a diagnosis on the Public Communication of Science established from this program, but also guidelines for changes in posture and for the resumption of an integrated communication process between higher administration, teaching (undergraduate and graduate -graduation), institutional communication, research and extension. Through the outlined recommendations, the university could give a new future to “UFG em Todo Lugar” and reframe the way it interacts with society based on it.